Proceedings of the 13th International Conference on Software Technologies 2018
DOI: 10.5220/0006906906640671
|View full text |Cite
|
Sign up to set email alerts
|

Formal Verification for Advanced Sensing Applications: Data Pre-processing in the INSPEX System

Abstract: Abstract:The INSPEX project aims to miniaturize state-of-the-art obstacle detection technology comprising heterogeneous sensors and advanced processing, so that it can be used for wearable devices. The project focuses on enhancing the white cane used by some visually impaired and blind people. Due to high demand for reliability and performance, the project is a good candidate for the use of formal methods. In this paper, we report lessons we have learned from formal modelling exercises related to the pre-proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In Lesecq et al, 6 there is a broad overview of the INSPEX Project from a medical instruments perspective. In Razavi et al 8 and Banach et al, 9 preliminary experience of the modelling of the data pathway was reported; this was subsequently extended to the lower level models included in the present paper. The paper 10 presents an overview of the project, and of early experience in the application of formal techniques, for a mixed commercial/technical audience.…”
Section: Section 11 Concludesmentioning
confidence: 83%
“…In Lesecq et al, 6 there is a broad overview of the INSPEX Project from a medical instruments perspective. In Razavi et al 8 and Banach et al, 9 preliminary experience of the modelling of the data pathway was reported; this was subsequently extended to the lower level models included in the present paper. The paper 10 presents an overview of the project, and of early experience in the application of formal techniques, for a mixed commercial/technical audience.…”
Section: Section 11 Concludesmentioning
confidence: 83%